Application of Good Governance Principles to Employee Work Effectiveness (Study at Makassar City Council Secretariat) - Asrina Basri; Rifdan Rifdan; Haerul Haerul (Universitas Negeri Makassar, 2023)
The public organization of each local government in carrying out the implementation of regional autonomy requires human resources, namely local government officials who are able to realize the characteristics of good governance. This study aims to determine; how good is the application of the principles of good governance at the Makassar City DPRD Secretariat, how high is the level of effectiveness of employees at the Makassar City DPRD Secretariat, and how much influence does the application of good governance principles have on employee effectiveness at Makassar City DPRD Secretariat. This type of research is quantitative with using a descriptive and correlational approach. Data collection techniques were carried out through interviews, questionnaires and documentation. Data analysis technique used is data analysis used is descriptive statistical analysis and inferential statistical analysis using simple regression for hypothesis testing. The results of the study show that the level of application of the principles of good governance which focuses on one principle, namely the principle of transparency at the Makassar City DPRD Secretariat, is classified as good category, this is viewed from informativeness, openness, and disclosure). The level of employee effectiveness is in the good category, in terms of alertness, absenteeism, motivation, job satisfaction, workload, and time to complete tasks. There is a significant effect of the application of the principles of good governance on the effectiveness of the work of employees at the Makassar City DPRD Secretariat.